Improving mothers’ knowledge by a training on the making of snack bar from taro flour and kepok banana - tiar lince bakara; Rumida; Gi Siahaan (Talenta Publisher Universitas Sumatera Utara, 2025)
The utilization of local food resources is an important strategy to support food security, improve nutrition, and empower communities. Bangun Rejo Village, Tanjung Morawa Subdistrict, Deli Serdang Regency, has abundant local food resources such as taro and kepok banana that have not been optimally utilized. This community service program aimed to improve the knowledge, attitudes, and practices of mothers with children under five years old and PKK cadres regarding the production of snack bars made from taro flour with the addition of kepok banana as a local food ingredient. The program was implemented through several stages, including socialization, pre-test, nutrition and local food education, hands-on training and demonstration of snack bar production, independent practice by participants, and post-test evaluation. A total of 25 participants took part in the activity. The results showed an increase in the average knowledge score from 63.20 before the training to 78.40 after the training. The proportion of participants with good knowledge increased from 16% to 76%. Participants’ attitudes toward local food processing were already positive prior to the intervention and remained positive after the training. These findings indicate that practical, community-based education and training using local food resources are effective in strengthening knowledge and skill capacity of community, particularly among mothers of young children, to produce nutritious and practical food products.